(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
This chapter presents the background to the project, details of the coring programme and the technique of tapestry excavation (excavation of a strip of deposits along an exposed face), excavation methodology, data management, methods for observation and interpretation and presentation of results.